PEMBUATAN SABUN PENCUCI PIRING SEBAGAI PELUANG USAHA BAGI IBU PKK DUSUN PUTAT WETAN, DESA PUTAT, KECAMATAN PATUK, GUNUNGKIDUL - Eka Sulistyaningsih; Indah Pratiwi Pakpahan (LPPM IST AKPRIND Yogyakarta, 2020)
The need for dish soap has increased because most people have started to abandon the traditional way of using scrubbing ash to wash dishes and switch to liquid dish soap. This causes the need for the procurement of soap which requires a lot of money. Seeing this opportunity, there are many liquid soap products that can be found in various types of markets. The purpose of this community service activity is to provide knowledge and training on making liquid dish soap in the context of community empowerment (in this case the PKK women's group). The method used in this community service activity is discussion, exposure and the practice of making dish soap. The participants were very enthusiastic about participating in the dish soap making training. With this training, participants can save expenses and start a new business producing dish soap to increase income.